Contrast Enhanced Ultrasound of a Gallbladder Lesion in a Patient with a History of Renal Cell and Rectal Cancer. (26th June 2013) - Reiser, Markus; Oehmen, Frank; Walter, Hajo; Büsing, Martin
Abstract : The gallbladder is an uncommon site of metastatic cancer. Although ultrasound can be regarded as a first line investigation for the detection of gallbladder lesions, differentiation between benign and malignant tumors usually requires resection. Real-time contrast enhanced ultrasound (CEUS) is a well-established technique for the classification of liver, pancreatic, and renal diseases (Weskott, 2008). The application of CEUS in the diagnosis of gallbladder tumors has rarely been described. We report the application of contrast enhanced ultrasound for the characterization of a gallbladder lesion in a 63-year-old patient with a history of renal cell and rectal cancer.